2007
DOI: 10.1007/s11524-007-9196-0
|View full text |Cite
|
Sign up to set email alerts
|

Exploring “Wine Shops” as a Venue for HIV Prevention Interventions in Urban India

Abstract: Addressing male heterosexual risk is a high priority for HIV prevention efforts in India. Particularly in urban India, which draws men for employment opportunities, these efforts are gaining momentum with a focus on understanding possible risk facilitators such as alcohol use. However, little is known about venues where such efforts might be targeted. In this paper, we explore community-based alcohol outlets or Bwine shops^in Chennai, India, as potential venues. We conducted ethnographic research with wine sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…This was similar to another community-based cross-sectional survey near Chennai in South India [9]. The reason for this could be that females are inhibited to disclose their alcohol use if any due to the social norms that stigmatize women drinkers and there is an extreme gender difference and prevalence among women which has consistently been estimated at <5% [22]. As per the estimates of National Survey Drug Abuse, 2004, there is an extreme gender difference and prevalence among women has consistently been estimated at <5%.…”
Section: Discussionsupporting
confidence: 80%
“…This was similar to another community-based cross-sectional survey near Chennai in South India [9]. The reason for this could be that females are inhibited to disclose their alcohol use if any due to the social norms that stigmatize women drinkers and there is an extreme gender difference and prevalence among women which has consistently been estimated at <5% [22]. As per the estimates of National Survey Drug Abuse, 2004, there is an extreme gender difference and prevalence among women has consistently been estimated at <5%.…”
Section: Discussionsupporting
confidence: 80%
“…We have reported detailed descriptions of wine shops earlier (Sivaram et al, 2007). Men visited wine shops at least thrice weekly and represented individuals from all walks of life.…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, CPOLs are individuals whose friends and close associates look to for advice, affirmation and counsel (Kelly, 2004). The considerable formative research that accompanied identifying and recruiting study participants in this trial found that male wine shop patrons and female sex workers who solicited clients at these venues were are highest risk for infection (Sivaram, et al, 2007;. The current study was an attempt to gain a deeper understanding of the risks of FSWs in Chennai.…”
Section: Sample and Data Collectionmentioning
confidence: 99%